1983
DOI: 10.1300/j024v06n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic Adolescents and Substance Abuse:

Abstract: The purpose of this article is to provide an understanding of the present state of knowledge about the probIem of substance abuse among Hispanic youth and to identify issues with which researchers, clinicians, administrators, and policy makers will have to deal in the coming decade. To do so, it will focus on five major areas: (1) the limitations of drug-related statistics; (2) demographic characteristics of Hispanics in the United States; (3) a review of the literature on Hispanic adolescent substance abuse; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…For example, ten years ago Latina adolescents were using drugs at a level lower than males (Human and Delgado, 1983). However, recent research has found that adolescent Latinas now use drugs at the same levels as males (ONDCP Report, 1997, Nuestra Juventud Project, 1998.…”
Section: Knowledge/conocimientomentioning
confidence: 99%
“…For example, ten years ago Latina adolescents were using drugs at a level lower than males (Human and Delgado, 1983). However, recent research has found that adolescent Latinas now use drugs at the same levels as males (ONDCP Report, 1997, Nuestra Juventud Project, 1998.…”
Section: Knowledge/conocimientomentioning
confidence: 99%